Friend-Guard Textfooler Attack on Text Classification System - Hyun Kwon (IEEE Access, 2025)
Deep neural networks provide good performance for image classification, text classification, speech classification, and pattern analysis. However, such neural networks are vulnerable to adversarial examples. An adversarial example is a sample created by adding a little noise to the original sample data and that, although presenting no change identifiable to human perception, will be misclassified by a deep neural network. Most studies on adversarial examples have focused on images, but research is expanding to include the field of text. Textual adversarial examples can be useful in certain situations, such as when models of both friend and enemy coexist, as in a military scenario. Here, a specific message may be generated as an adversarial example such that no grammatical or semantic problems are apparent to human perception and it will be correctly classified by the friend model but incorrectly classified by the enemy model. In this paper, I propose a “friend-guard” textual adversarial example for a text classification system. Unlike the existing methods for generating image adversarial examples, the proposed method creates adversarial examples designed to be misclassified by an enemy model and correctly classified by a friend model while retaining the meaning and grammar of the original sentence by replacing words of importance with substitutions. Experiments were conducted using a movie review dataset and the TensorFlow library. The experimental results show that the proposed method can generate an adversarial example that will be correctly classified with 88.2% accuracy by the friend model and 26.1% accuracy by the enemy model.